Policy family misalignment in a family resilience program: a qualitative KAP study of motekar - Herny Novianti; Ilfiandra Ilfiandra; Yusi Riksa Yustiana; Tina Hayati Dahlan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Family resilience programs are widely implemented as community based interventions. However, their effectiveness in structurally vulnerable contexts, particularly among single parent households, remains insufficiently theorized and empirically validated. This study addresses this gap by examining the alignment between program design, implementation processes, and beneficiaries’ lived experiences in the Motekar (Motivator Ketahanan Keluarga) Program in RW 17 Kriyan Barat, Cirebon City. A qualitative case study design was employed using purposive sampling, involving 25 single parents, 25 adolescents, and 3 policy stakeholders. Data were collected through non-participant observation, in-depth semi-structured interviews, and document analysis, and analyzed using iterative coding procedures (open, axial, and selective coding) with constant comparative analysis, guided by the Knowledge–Attitude–Practice (KAP) framework. The findings reveal three critical patterns: (1) structural misalignment between standardized program design and context-specific family needs; (2) discontinuity in mentoring processes that weakens program sustainability; and (3) ambiguity in facilitators’ operational roles. In addition, a divergence between policy-based evaluation indicators and beneficiaries’ lived experiences indicates limitations in standardized assessment approaches. This study contributes by proposing a context-sensitive and participatory evaluation perspective to strengthen the effectiveness of family resilience programs in vulnerable family settings.